Managerial economics - "Dean , Joel" (New Delhi, 1987)
The purpose of this book is to show how economic analysis can be used in formulating business policies. The book draws upon economic analysis for the concepts of demand, cost, profit, competition and so on, that are appropriate for the development, of an economic approach to executive decisions. Although the text is preoccupied with concepts rather than detailed techniques of estimation, it concentrates on those concepts that can be measured and applied to management problems. The book does not attempt to cover all aspects of either management or economics: it deals with those phases of enterprise economics that are particularly useful to the management of a large industrial corporation. The author$1 (Bs endeavour successfully bridges the gap between the problems of logic that intrigue economic theorists and the problems of policies that plague practical management needs in order to give executive access to the practical contributions that economic thinking can make to top-management policies.s